A Review Low Strain Integrity Testing Practices In India And Complexities Involved In Evaluation Of Test Results - RavikiranVaidya; Vishal Dhamecha (Deep Foundations Institute, 2022)
Low Strain Pile Integrity Testing has been used in India since 1990’s and several have tried to demonstrate the utility and benefits of this method. However, use of this technology was limited till 1998 as not enough data maybe was not available to justify its use and application on major infrastructure and real estate projects. The first author has done significant work in this method resulting in its use in practically all sectors of the industry that use concrete bored pile foundations as a supporting element. The paper explains various signal enhancers or modifiers involved in processing of low strain test data and its implication on the final output. It also describes how the method can lead to abuse or can provide poor interpretation if incorrectly used. The current effort is to demonstrate that data collection and evaluation becomes complex with changes in soil stratum and pile profile. The paper highlights the present testing practices and provides a guideline for classification of pile integrity into few simple categories in Indian context rather than writing complex interpretations.